2004
DOI: 10.1002/cjce.5450820222
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer to an Isolated Bubble Rising in a High‐Temperature Incipiently Fluidized Bed

Abstract: point antérieurement a été étendu de façon à inclure le fonctionnement à température élevée.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In Table , the heat-transfer coefficients obtained from simulations are compared with those of the Davidson–Harrison model given by eq . Also, the experiments reported in ref for 0.25 and 0.5 mm sand particles have been included in Table for comparison. It can be observed that the simulations give much higher values in comparison with the values obtained from the Davidson and Harrison bubble model (approximately twice as large).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table , the heat-transfer coefficients obtained from simulations are compared with those of the Davidson–Harrison model given by eq . Also, the experiments reported in ref for 0.25 and 0.5 mm sand particles have been included in Table for comparison. It can be observed that the simulations give much higher values in comparison with the values obtained from the Davidson and Harrison bubble model (approximately twice as large).…”
Section: Resultsmentioning
confidence: 99%
“…However, such noninvasive radiative techniques are limited to pseudo-2D bed studies and cannot be used for 3D beds. Fluidized-bed hydrodynamics in 3D has been studied experimentally using emission-computed and X-ray tomography techniques. , Furthermore, measurements utilizing probes have been performed to study heat transfer in rising bubbles in 3D fluidized beds, e.g., by ref . In their study, heat-transfer coefficients for rising bubbles in fluidized beds of smaller particles in the range 250–500 μm were reported.…”
Section: Introductionmentioning
confidence: 99%